The Liveworksheets in Vocabulary Learning: Implementation and Perception of EFL Students - Dewi, Ni Nyoman Risa Aryana (The Art of Teaching English as a Foreign Language (TATEFL), 2025)
This study investigates the implementation of the Liveworksheets application in vocabulary learning for 8th-grade students at a public high school in Bali and explores students’ perceptions of its use. While existing literature has primarily emphasized the technical features of Liveworksheets and its general application in language learning, there remains a significant research gap in understanding how this tool is practically integrated into vocabulary instruction within offline classroom settings—particularly in Indonesian secondary education—and how students perceive its effectiveness. To address this gap, this research employs a descriptive qualitative approach, incorporating document analysis, classroom observations, questionnaires, and in-depth interviews with an English teacher and students. The findings reveal that Liveworksheets is used mainly as a formative assessment tool, supporting vocabulary retention through features such as automatic feedback and interactive formats. Students identified benefits such as personalized learning, ease of access, and increased motivation, though challenges related to internet connectivity and device limitations persist. This study contributes practical insights into the pedagogical use of interactive digital worksheets in vocabulary learning, particularly in offline classroom environments in Indonesia.